The Proportion of Cropland Influences Negatively the Occurrence of Breeding Birds in an Alkali Grassland Habitat in NW Serbia - Dapic, Dejan; Méro, Thomas Oliver (Acrocephalus, 2016)
Grasslands host a high diversity of plant and animal species. In Serbia, most alkali grasslands are located in the province of Vojvodina. The majority are not subject to conservation. The aim of the study was to investigate the relationship between the proportion of croplands and (1) the number of breeding species and (2) the number of breeding pairs in the alkali grasslands of the upper Mostonga River catchment basin (NW Serbia). The size of the study area was 400 ha. Birds were surveyed along seven parallel transects eight times per breeding season. Lengths of the cross sections of both grasslands and croplands were measured. The proportion of croplands per transect was calculated by dividing the total length of cross sections of croplands by the total length of transect. The relationship between the proportion of croplands and the number of breeding pairs and the number of breeding species, respectively, was studied using simple linear regression. We recorded a total of 171 nesting pairs belonging to 23 species in the alkali grassland investigated, with breeding densities between 2.2 and 10.3 pairs per 10 ha. The number of species per transect ranged between 6 and 11. The most abundant species were Skylark Alauda arvensis, Yellow Wagtail Motacilla flava and Corn Bunting Emberiza calandra. The numbers of breeding pairs (F = 21.761, P < 0.0001) and of breeding species (F = 13.758, P = 0.001) were both influenced negatively by the proportion of croplands. These findings highlight the need for coordinated conservation measures on the alkali grasslands of Vojvodina.